Preparation and in vitro characterization of SN-38-loaded, self-forming polymeric depots as an injectable drug delivery system - Chawan Manaspon (2018)
This work describes the preparation and characterization of anticancer-loaded injectable polymeric depots that consisted of d,l-lactide (LA), ε-caprolactone (CL), and poly(ethylene glycol) (PEG) or [poly(ε-caprolactone)-random-poly(d,l-lactide)]-block-poly(ethylene glycol)-block-[poly(ε-caprolactone)-random-poly(d,l-lactide)] (PLEC) copolymers for malignant gliomas treatment. PLECs were polymerized with different percentages of LA to deliver 7-ethyl-10-hydroxycamptothecin (SN-38), a highly potent anticancer drug. SN-38-loaded depots could form directly in phosphate buffer saline with more than 98% encapsulation efficiency. The release rate of SN-38 from depots was found to depend on the amount of LA in PLECs, loading content of SN-38 in the depots, and depot weight. Encapsulation of SN-38 inside depots could enhance the stability of SN-38 where all of SN-38 released after 60 days was in an active form. Depots without SN-38 were evaluated as noncytotoxic against U-87MG, whereas SN-38-loaded depots showed cytotoxic effect as a function of concentration. © 2012 Wiley Periodicals, Inc.